Cardiovascular manifestation in COVID-19 infection in a patient with rheumatoid arthritis: case report (Research, Society and Development, 2021)
This study aimed to report the case of a 65-year-old female patient with a previous diagnosis of rheumatoid arthritis, among other comorbidities that corroborate the increase in cardiovascular risk, seen in 2020 in a private hospital in Belém, due to picture of acute coronary syndrome associated with SARS-Cov-2 virus infection. Due to the clinical profile, the patient underwent an electrocardiogram that showed myocardial infarction with ST-segment elevation alteration, indicating the need for reperfusion therapy, oxygen therapy and monitoring of vital signs. A chest CT scan showed a “ground glass” pattern and involvement of more than 25% of the lung parenchyma and evolved with thrombosis of the femoral artery. After treatment in the intensive care unit, he was discharged from the health service, remaining stable from a rheumatological, cardiovascular and pulmonary point of view.